2020
DOI: 10.1016/j.ecosys.2019.100730
|View full text |Cite
|
Sign up to set email alerts
|

Growth and real business cycles in Vietnam and the Asean-5. Does the trend shock matter?

Abstract: We examine Vietnam's economy together with its closest trade partners. We show that capital accumulation has been the primary growth engine since the start of its transition to the pro-market economy in 1986-the Doi Moi. We also show that the cyclical behavior of its macro aggregates is similar to the one of its ASEAN-5 peers and other developing countries. We extend the standard small-open-economy RBC model by considering habit persistence and government consumption which allows a close match of the moments o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 44 publications
1
1
1
Order By: Relevance
“…positive responses on the real product, private consumption and private fixed investment to a great extent. At the same time, the productivity shocks strongly and persistently affect the product in Bolivia (Vargas, 2010) and these results are consistent, as found by Pham, Sala, and Silva (2020) who demonstrated that productivity shocks explain more than 50% of the variability of output growth, such as in the Vietnamese economy.…”
Section: Implications Of Domestic Shockssupporting
confidence: 80%
“…positive responses on the real product, private consumption and private fixed investment to a great extent. At the same time, the productivity shocks strongly and persistently affect the product in Bolivia (Vargas, 2010) and these results are consistent, as found by Pham, Sala, and Silva (2020) who demonstrated that productivity shocks explain more than 50% of the variability of output growth, such as in the Vietnamese economy.…”
Section: Implications Of Domestic Shockssupporting
confidence: 80%
“…It contributes about 71% and 67% of the variability in output in the medium and long term, respectively. This is followed by labor supply accounting at about 15% in the medium term and 20% in the long run Our finding that investment shock is the main determinant of output variability contradicts Pham et al (2020), who asserted that risk premium is the key driver of Thailand's business cycle. However, our results confirm their finding that productivity shock accounts for about one fourth of output growth variation.…”
Section: Forecast Error Variance Decompositioncontrasting
confidence: 68%
“…In this sense, one of the most interesting research topics in economics is the measurement of business cycles (BCs) and the identification of their determinants. Aspects such as co-movements, synchronization and the determinants of BC have been widely analyzed in theoretical studies (Pham et al, 2020) and empirical ones (G omez-Loscos et al, 2020).…”
Section: Introductionmentioning
confidence: 99%